Accurate hydrogen parameters for the amino acid l‐leucine. Issue 6 (2nd December 2016) - Binns, Jack; Parsons, Simon; McIntyre, Garry J.
Abstract : Modern neutron Laue diffraction has been used to determine the structure of the primary amino acidl ‐leucine. Abstract : The structure of the primary amino acidl ‐leucine has been determined for the first time by neutron diffraction. This was made possible by the use of modern neutron Laue diffraction to overcome the previously prohibitive effects of crystal size and quality. The packing of the structure into hydrophobic and hydrophilic layers is explained by the intermolecular interaction energies calculated using the PIXEL method. Variable‐temperature data collections confirmed the absence of phase transitions between 120 and 300 K in the single‐crystal form.